Métodos contracetivos reversíveis de curta e longa duração - Câmara, Sara (2016)
ABSTRACT Overview: The daily pill, a short-acting reversible contraceptive (SARC), is more used than long-acting reversible contraceptives (LARC) though these are highly effective, safe and less dependent on women use. It is important to identify which differences between SARC or LARC users can justify this choice. Aims: Describe and compare the two types of contraceptive methods users (age, marital status, previous history of pregnancy, level of education, age at which the method was started, level and source of knowledge, medical advice and level of satisfaction with the information received). As a secondary objective, we aimed to identify the existence of myths and misbeliefs about contraception and the reasons for choosing or discontinuation of the contraceptive method. Study Design: Observational and retrospective. Population: Women who use or had used contraception, aged 18 -50 years. Methods: A self-report and anonymous questionnaire, available in primary health care centers and hospitals. Results: In a group of 300 women, with a median of 35,6 years (18 - 50 years; s = 8,3 years), 68% (203/300) were using a contraceptive method and 28% (83/300) were no longer using it . Among these, 75% were using SARC or these corresponded to the last method used. Single women prevailed in the SARC group (p=0,002) and those with a previous pregnancy prevailed in the LARC group (p=0,002). No other statistically significant differences were identified. 86% (237/274) had a medical consultation before beginning to use a contraceptive, and 59% (139/237) were very satisfied with the information received. The control of the menstrual cycle was important for SARC users whether the using facility was important for LARC users. Conclusions: Although effective and safe, LARC where less prevalent in our study. History of previous pregnancy was the only clinically significant difference between SARC and LARC users..